The Problem of an Animal in Contemporary Philosophy: Toward the Withdrawal of the difference between Human and Animal - Baranovas, Ruslanas (Religija ir kultūra, 2014)
In this article, the problem of an animal in contemporary philosophy is analyzed, while researching the productivity of the philosophical term of the difference between human and animal. In this article, three criteria of animal research are discussed: (1) the ability to say something positive about an animal, (2) the non-anthropologic discussion about an animal and (3) the ethical consequences of thinking about an animal. I state that the difference between human and animal is not the most productive strategy of working with the question regarding animals. In this article, Martin Heidegger’s and Jacques Derrida’s accounts of animals are overviewed and criticized. A more productive view of Catherine Malabou is put forward. In the end of the article, it is showed how the position of Malabou, based on her interpretation of Hegel, opens up the epigenetic side of Georg Hegel’s philosophy itself.
Keywords: animal; difference; non-difference; Heidegger; Derrida; Malabou; Hegel